Respostas

2013-08-21T14:38:19-03:00
4x² - 12x + 9 = 0 ......a = 4......b = - 12......c = 9

x = [- b ± √(b² - 4ac) ] / 2a

x = [ 12 ± √(-12)² - 4.4.9) ] / 2.4

x = [ 12 ± √(144 - 144) ] / 8

x = [ 12 ± 0 ] / 8

x = 12/8 = 3/2

S: { 3/2 }
13 3 13
espero q entenda,o x' e o x" deram resultado igual pois o delta deu 0...
2013-08-21T14:44:01-03:00
4x²+9=12x 
4x²-12x+9=0
/\=b²-4.a.c
/\=(-12)²-4.4.9
/\=144-144
/\=0
x=-b+-
√/\
       2.a
x=-(-12)+-√0
        2.4
x=12+-0
       8
x'=12+0=12=6=3
       8      8   4  2
x"=12-0=12=6=3
       8     8   4   2 
29 4 29